Trophy Hunting and Possible Source-Sink Dynamics in Protected Areas: Insights from Trophy Size and Offtake Patterns in Southeast Zimbabwe - Jeke, Augustine; Chanyandura, Admire; Muposhi, Victor K.; Madhlamoto, Daphine; Gandiwa, Edson (International Journal of Zoology, 2019)
Developing harvest management strategies in designated hunting areas requires systematic and robust monitoring. We assessed the trophy size, quota utilization, and distribution of kill sites of African elephant, Cape buffalo, greater kudu, and leopard for the period 2007-2014 in Malapati Safari Area, southeast Zimbabwe. Trophy sizes for African elephant significantly increased over time albeit being below the expected minimum Safari Club International (SCI) score. Cape buffalo trophy sizes declined significantly over time but were not different from the SCI minimum score. However, greater kudu trophy sizes were higher than the SCI minimum score despite being constant over time. Leopard trophy sizes were higher than the SCI minimum score and increased with time. Quota utilization for African elephant and Cape buffalo increased while that of greater kudu and leopard did not change between 2007 and 2014. Some kill sites, in particular, for the African elephant and Cape buffalo, were within the buffer area with the state protected area, i.e., Gonarezhou National Park. Increased hunting pressure likely leads to poor trophy quality and hunting within the protected buffer areas. In contrast, effective adherence to hunting ethics and scientifically and conservatively set quotas largely does not compromise the trophy quality of harvested species. The observed trophy size patterns and kill sites distribution suggest the possible existence of source and sink dynamics of trophy species occurring in a protected area complex within the Zimbabwe’s component of the Greater Limpopo Transfrontier Park. To ensure sustainable trophy hunting in the study area and similar ecosystems the following are recommended: (i) scientifically robust, adaptable, and participatory quota setting process, (ii) enhanced adherence to good practice in terms of ethical hunting conduct, and (iii) development of a robust hunting monitoring system covering all elements of hunting for adaptive wildlife management.